Gender dimension in social business: the experiences of Lithuanian women social entrepreneurs - Novelskaitė, Aurelija; Pučėtaitė, Raminta; Pušinaitė-Gelgotė, Rasa (Information & Media, 2018)
This paper explores how women – social entrepreneurs – perceive the mission of their social businesses and the effects of gender in the context of such businesses. An analysis of interviews (n=18) with representatives of social businesses in Lithuania reveals that the mission of a social business is either strongly pragmatic (in the organizations that have the legal status of a social enterprise), dissociated from social impact or a rather vague one but that emphasizes goodwill. Meanwhile, the gender dimension in social businesses is approached in rather stereotypical ways: the effect of gender is either ignored or interpreted by stereotypically separating the traditionally female (e.g., caring for and bringing up children) and male (e.g., engineering) fields of activities.